Registration of pharmaceuticals: expert assessment of modification the standard documentation - T V Kartavtsova; A V Fomina (RUDN Journal of Medicine, 2015)
Registration of drugs is a key element in the system of state regulation of the pharmaceutical market. This paper discusses the expert assessment of changes to the registration documents for drugs, the basic directions of improvement of the system changes in the regulatory documents.